High-rate OVPE-GaN crystal growth at a very high temperature of 1300 °C. (1st March 2022) - Shimizu, Ayumu; Usami, Shigeyoshi; Kamiyama, Masahiro; Kawanami, Itsuki; Kitamoto, Akira; Imanishi, Masayuki; Maruyama, Mihoko; Yoshimura, Masashi; Hata, Masahiko; Isemura, Masashi; Mori, Yusuke
Abstract: Polycrystal formation is an issue to be resolved to grow thick GaN crystals by the oxide vapor phase epitaxy (OVPE) method. Since the high-temperature growth at 1250 °C was effective in suppressing the polycrystal formation in our previous study, we attempt further high-temperature OVPE-GaN crystal growth at 1300 °C. However, the GaN surface decomposition becomes severe at 1300 °C. The pre-growth epitaxy was employed to avoid surface decomposition and enable high-temperature growth. Nearly polycrystal-free growth of GaN crystal was achieved, and we obtained a 478 μ m thick OVPE-GaN layer at 1300 °C with a further high growth rate of about 200 μ m h −1 .